Muscle Insulin Resistance in Youth with Obesity and Normoglycemia is Associated with Altered Fat Metabolism. Issue 12 (28th October 2019) - Cree‐Green, Melanie; Wiromrat, Pattara; Stuppy, Jacob J.; Thurston, Jessica; Bergman, Bryan C.; Baumgartner, Amy D.; Bacon, Samantha; Scherzinger, Ann; Pyle, Laura; Nadeau, Kristen J.
Abstract : Objective: This study aimed to phenotype and compare adipose, hepatic, and muscle insulin sensitivity (IS) in a diet‐ and physical activity–controlled cohort of normoglycemic youth with obesity with that of participants without obesity (controls) to distinguish early metabolic abnormalities in pediatric obesity. Methods: Thirty‐eight participants (17 in the control group [BMI < 85th percentile] and 21 youth with obesity [BMI ≥ 95th percentile]; age: 12‐21 years; 76% female; Tanner stage 4‐5; sedentary) were enrolled. Tissue‐specific IS was measured using a four‐phase hyperinsulinemic‐euglycemic clamp with glucose and glycerol isotope tracers to assess suppression of endogenous glucose release and lipolysis by insulin. Intramyocellular lipid content was assessed by 1 H–magnetic resonance spectroscopy, and hepatic fat fraction (HFF) and visceral fat were assessed by magnetic resonance imaging. Calf‐muscle mitochondrial activity was measured with exercise‐stimulated 31 P–magnetic resonance spectroscopy. Results: Youth with obesity had higher HFF ( P < 0.001), visceral fat ( P = 0.024), and intramyocellular lipid content ( P = 0.017) and lower muscle (glucose clearance rate [ P < 0.001]), adipose ( P < 0.0001), and hepatic IS ( P < 0.003). Mitochondria postexercise response was not different. In participants with obesity, muscle IS inversely correlated with HFF ( r = 0.700, P = 0.002) and suppressed free fatty acid concentrations ( r = −0.65, P = 0.003). Conclusions: Inactive normoglycemic youth with obesity had decreased muscle, adipose, and hepatic IS. Free fatty acids and liver fat were inversely associated with muscle IS, which argues for lipid‐targeted interventions.